Religious Education Model Based on Local Wisdom to Strengthen Cultural Identity - Faiha, Bahiyya Atiqa (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2024)
This study aims to explore and develop a religious education model based on local wisdom to strengthen students' cultural identity. The research employs a qualitative method using a literature review (library research) approach. Data were collected by analyzing various sources, such as books, academic journals, scholarly articles, and relevant documents related to the research theme. The findings indicate that religious education based on local wisdom has significant potential to shape students' character in alignment with local cultural values. This approach not only enhances students' understanding of religious teachings but also fosters a sense of pride and love for their own culture. Additionally, integrating local wisdom into religious education serves as a medium for preserving cultural heritage amidst the wave of globalization, which increasingly erodes local identities. This education model emphasizes contextual, adaptive, and value-based learning strategies, such as incorporating folklore, local traditions, and region-specific religious practices. Thus, religious education rooted in local wisdom offers an innovative solution to strengthen students' cultural identity without neglecting spiritual aspects. The study recommends collaboration between educators, religious leaders, and local communities to effectively implement this model. Furthermore, educational policies supporting the integration of local wisdom into the curriculum are essential to ensure the sustainability of this approach.